From domestic apotropaic magic to state religion in the Roman world: ways there and back - Nuño, Antón Alvar (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
There are two main methodological approaches in relation to the study of apotropaic magic in the Graeco-Roman world. An historicist one, focused on the formal description of the data and on tracing their possible origins; and a psychologist-functionalist one, which interprets the data as a psychological relief to the anxieties produced by the misfortunes of dailylife. I propose to explore here an aspect of apotropaic magic frequently overlooked: its mutual relation with the religion of the State, which creates a common syntactic framework but also tensions and conflicts.